Teori Fitrah dan Pengembangan Agama Anak - Lubis, Rahmat Rifai; Gusman, Media (Al-Fikru: Jurnal Ilmiah, 2021)
Humans are religious creatures, so called because God grants Fitrah from the very beginning of human life. Fitrah becomes a special potential in humans, because it directly becomes the creation of Allah and is directly installed by Allah in man, since humans are in the spirit realm.Even though they have had the nature since the beginning of their creation, the nature must still be maintained especially when the child is at an early age. At this time was touted as the golden age. Success in maintaining fitrah at an early age, will lead to success in the future. Many methods that can be used to maintain this nature include the method of advice, exemplary methods, methods of habituation, and methods of stories or fairy tales.